POLITICAL DOWNLINE AND NCHINDAISM IN THE GLOBAL POLITICAL ECONOMY: Senior Lecturer/Researcher - Keming, David Nchinda (Advances in Social Sciences Research Journal, 2021)
The study focuses on the gambit of capitalism (political downline) and its relationship with the theory of Nchindaism. It provides an understanding to the exploitative mechanics of capitalists on the less developed and predicts the pendulum from Western controlled capitalism to military alliances where Western countries are elbowed from masters to actors and the possible collapse of the United Nations (UN). It targets: derivation, connotation, motives, manoeuvre/repercussions of capitalism, its drift, insight of Nchindaism & International Relations theories. The study is realised with primary, secondary and tertiary data under the ambit of qualitative methodology. Our findings reveal that the myth of None-Proliferation of Weapons of Mass Destruction and the abusive application of Veto Rights by the Big Five within the UN Security Council (UNSC) catalysed nuclear polarisation leading to the regress of Western capitalism and the emergence of ideological military alliances. It argues that as long as the notion of state sovereignty is built on mutual respect, equality and none-interference in internal affairs, state’s capabilities and defence mechanics shouldn’t face restrictions from others or organisations if it doesn’t deter human rights and welfare. It concludes that since the evolution of science is a free gift from nature and growth of the human mind, education on nuclear responsibility should take preference rather than the myth of limitation to its development or acquisition.